14C-Methylamine-glutaraldehyde conjugation as an alternative to iodination for protein labeling. (August 2003) - Moore, Penelope L.; Damelin, Leonard H.; Harrison, Tim J.
Radiolabeling of native proteins conventionally has required iodination using 125 Iodine ( 125 I). Although radioiodination can result in high specific activity, there are several drawbacks in the use of 125 I (e.g., radiological hazards and short half-life). 14 C-Methylamine-glutaraldehyde conjugation to proteins offers an alternative for radiolabeling of proteins that is safer and longer-lived. α-2-Macroglobulin was radiolabeled by conjugation to a 14 C-methylamine-glutaraldehyde conjugate. Analysis of the labeling procedure was performed using scintillation counting, gel filtration chromatography, and protein assays. The radiolabeled α-2-macroglobulin was activated using established protocols and tested for functional integrity using competitive binding assays in the presence of recombinant receptor associated protein, an alternative ligand for the α-2-macroglobulin cellular receptor. The function of α-2-macroglobulin was unaffected by the labeling procedure. Comparison of 14 C-methylamine-labeling and iodination by Scatchard analysis yielded nonlinear plots that suggested the presence of two sets of receptors with different binding affinities but that do not show cooperativity. This technique offers an alternative to radioiodination for the sensitive labeling of proteins.